Can Family Motivation Enhance Men’s Uptake of Cascade Screening for Familial Mutations? - Giulia Ongaro; Serena Petrocchi; Mariarosaria Calvello; Bernardo Bonanni; Irene Feroce; Gabriella Pravettoni (American Journal of Men's Health)
Pathogenic variants in the BRCA1 and BRCA2 genes increase the relative and absolute risks of developing breast, ovarian, prostate, and pancreatic cancer. Clinical guidelines recommend cascade screening (CS) to enhance the identification of at-risk relatives. Despite the benefits of CS in facilitating access to appropriate cancer screening and risk-reduction strategies, CS uptake remains relatively low, particularly among at-risk men. Men’s decisions regarding CS appear to be driven more by familial rather than individual disease risk, framing the decision as a family duty. Little is known about the motivational factors that could encourage men’s participation in CS. This randomized controlled trial aimed to evaluate the effectiveness of two first-person, gain-framed messages in promoting CS intention among at-risk men: one featuring a self-referred narrative (SM) and the other a family-referred narrative (FM). A total of 110 male first-degree relatives of female BRCA1/2 carriers were randomized into two groups. T -tests revealed no significant difference between groups in perceived message quality. Additionally, after controlling for age, the type of message received did not significantly influence participants’ levels of intention to undergo CS. These findings highlight the need for further exploration of the complex motivational factors influencing at-risk men’s adherence to CS. Future research should consider alternative health communication strategies tailored to different motivational drivers.